Cluster Based DDoS Detection Method in Data Mining (International Journal of Engineering and Computer Science, 2017)
Distributed denial of service attacks (DDoS) are a growing threat to business worldwide. By adopting new purpose built solutions designed specifically to detect and defeat DDoS attacks, businesses can keep their business operation running smoothly. Data mining algorithm is used presents a DDoS attack detection model. Experimental result source that DDoS attacks can be detected efficiently and swiftly.